PENGARUH KOMPOSISI DAN UKURAN PARTIKEL TERHADAP KUALITAS BRIKET KULIT DURIAN DAN TEMPURUNG KELAPA - Ashar, Muh.; Sahara, Sahara; Hernawati, Hernawati (JFT : Jurnal Fisika dan Terapannya, 2020)
Research has been carried out on the utilization of durian rind and coconut shell waste by turning it into bio briquette. This study aims to determine the amount of heat, water content and duration of combustion in order to obtain the best quality. Samples were made with the composition of durian rind, coconut shell, and tapioca flour as an adhesive. Each sample was carbonized with a combustion drum and furnished at a temperature of 2500C, then grinding, sifting, and molding were carried out. The composition variations used are (20:80)%, (40:60)%, (60:40)%, and (80:20)% with particle sizes of 100 mesh and 170 mesh, the adhesive mass used is 3 gr. The results of the study, testing the calorific value using the bomb calorimeter obtained the best quality in the composition (80:20)% with a size of 100 mesh of 6482,76 cal/gr, the results of testing the moisture content using an 1050C oven obtained the best quality in the composition (80:20)% with a 100 mesh size of 6,77% and the longest burning test with the longest burning duration in composition (20:80)% with a 170 mesh size of 211,8 minutes/gr.